Antibacterial Activity Peel-off Mask Ethanol Extract of Pomegranate Peel (Punica granatum L.) Against Staphylococcus epidermidis and Staphylococcus aureus - Evania, Arneta; Rakainsa, Senda Kartika (Universitas Negeri Semarang, 2023)
Background: Pomegranate peel (Punica granatum L.) is a part of the pomegranate fruit which is used as a traditional medicine for acne. The ethanol extract of pomegranate peel contains alkaloid, phenolic, flavonoid, and saponin compounds which have potential as antibacterial agents. Aim: This study aims to make peel-off masks of the ethanol extract of pomegranate peels and to determine the antibacterial activity of peel-off masks against acne-causing bacteria Staphylococcus epidermidis and Staphylococcus aureus. Material and Methods: The maceration method was used to obtain pomegranate peel extract with 96% ethanol solvent. Phytochemical screening is used to determine the content of the extract. Preliminary test of antibacterial activity was carried out using the disk diffusion method to determine the MIC value. The extract was then made into a peel-off mask preparation based on HPMC gel and PVA as a gelling agent. The peel-off mask was then evaluated physically and tested for its antibacterial activity by agar well diffusion. Results: Pomegranate peel (Punica granatum L.) extracted with 96% ethanol contains alkaloids, flavonoids, saponins, and phenolics which show antibacterial activity against Staphylococcus epidermidis and Staphylococcus aureus with a MIC value of 1.9 mg/ml. The results of observations of the physical properties of peel-off masks showed that the formulas that met the requirements were F(1) and F(2) with extract concentrations of 1.56% and 3.12%, respectively. The results of the antibacterial activity test of the peel-off mask of the ethanol extract of pomegranate peel had an inhibition zone of 9-15 mm in the medium to strong category. Conclusion: Based on the results of physical evaluation and antibacterial activity test, F(2) was the most optimum formula with inhibition against Staphylococcus epidermidis and Staphylococcus aureus of 13 mm and 14.5 mm, respectively.